Nanotechnology advances and real-life applications - Bhargava, Cherry, d 1982; Sachdeva, Amit (CRC Press / Taylor & Francis Press, 2020)
"This comprehensive reference text discusses advance concepts and applications in the field of nanotechnology. The text presents detailed discussion of key important concepts including nanomaterials and its synthesis, fabrication and characterization of nanomaterials, carbon-based nanomaterials, nano-bio interface and nanoelectronics. Three separate chapters discuss applications of nanotechnology in the fields of renewable energy, medicine and agriculture. The text will be useful for senior undergraduate and graduate students in the field of electrical engineering, electronics engineering, nanotechnology and nanoscience"